Results of a seismic reflection survey across the fault zone between the Thompson nickel belt and the Churchill Tectonic Province, northern Manitoba - Green, A. G. (Canadian Journal of Earth Sciences, 1981)
Approximately 11 km of four-fold common reflection point data have been recorded across a region that spans the contact fault zone between the Thompson nickel belt and the Churchill Tectonic Province. From these data it is shown that the upper crust in this region and, to a lesser extent, the lower crust are characterized by numerous scattered events that originate from relatively small-scale features. Within the Thompson nickel belt two extensive and particularly high-amplitude reflection zones, at two-way travel times of t = 5.0–5.5 s and t = 6.0–6.5 s, are recorded with apparent northwesterly dips of 0–20 °C. These reflection zones, which have a laminated character, are truncated close to the faulted contact with the Churchill Province. Both the contact fault zone and the Churchill Province in this region have crustal sections that are relatively devoid of significant reflectors. The evidence presented here confirms that the crustal section of the Thompson nickel belt is fundamentally different from that of the Churchill Tectonic Province.